Prevalance of major risk factors of non-communicable diseases among early adults in Kavrepalanchowk, Nepal. - Adhikari,Asmita (2020)
ABSTRACT: Background: Currently, NCDs are in the limelight replacing communicable diseases, which were the leading cause of death in most countries. Non communicable disease is the leading cause of death globally as well as SEAR. NCDs kill 38 million people each year. This study aims to estimate the prevalence of NCDs risk factors among early adult population. Methods: A cross-sectional study was conducted among early adults of Kavreplanchwok in Nepal. The study period was from 2019 May to September. Total samples 430 were recruited through multistage sampling. Self-administrated questionnaire was used for the data collection tool along with other tools which were used such as UNICEF electronic weighing scale and mechanical aneroid sphygmomanometer. Data were entered into EpiData (version3.1) software and analysis was performed with the help of the IBM Statistical Package for Social Sciences (SPSS version 22). The formal ethical permission was taken from Nepal Health Research Council (NHRC). Results: The prevalence of smoking was 11.9% and smokeless tobacco was 8.2%. Alcohol consumption practice among the adults was 26.6%. Family history of hypertension was seen higher than family history of diabetes and cancer. The prevalence of hypertension was 26.3%. Prevalence of additional salt intake was 35.6%. High prevalence of systolic BP (11.9%) and diastolic BP (23.6%) was found adult's. 39.7% adults where obese. Conclusions: In this study, high prevalence of unhealthy diet was observed which poses threat to health and wellbeing of individuals. At the same time, high salt intake and alcohol consumption along with high prevalence of obese and diastolic BP is worrisome. Keywords: Non-communicable diseases, adults, risk factors, Lifestyle practice